Um olhar para os registros cemiteriais: estudo nos documentos públicos de Santa Maria (RS) - Teixeira, João Alberto Licht (2020)
This present study originates from author’s personal concern about the treatment of documentary records of the cemeteries activities of the six public necropolises of the city of Santa Maria (RS) and the quantity and quality of the information made available to them. The temporal goal covers the range from 2017 to early 2020. This is a study on the analog and digital documents of municipal cemeteries in the urban area of Santa Maria (RS). As exploratory instruments, techniques of visits to cemetery documentary collections, informal interviews, observation and bibliographic research were used to identify the types of documents produced and received at such institutions and how users are given access to information. This work aimed to analyze how the records and information are organized in analog and digital documents of municipal cemeteries in the urban area of Santa Maria (RS).The final product of this work will be the elaboration of a heritage education proposal through different “Literatura de Cordel”, to be used as a cultural diffusion in public cemeteries in the city of Santa Maria (RS).